CeOx-modified NiFe nanodendrits grown on rGO for efficient catalytic hydrogen generation from alkaline solution of hydrazine. (2nd November 2017) - Men, Yana; Du, Xiaoqiong; Cheng, Gongzhen; Luo, Wei
Abstract: CeOx -modified NiFe catalysts with branched nanodendritic architectures have been successfully deposited on reduced graphene oxide (rGO) through a simple co-reduction method. Thanks to the synergistic electronic effect between Ni, Fe, and Ce, as well as dendritic morphology with a high number of active sites, the resulted Ni3 Fe-(CeOx )0.15 /rGO exhibited superior catalytic activity toward dehydrogenation of hydrous hydrazine in alkaline condition, with turnover frequency (TOF) values of 56.8 h −1, and 126.2 h −1 at 328, and 343 K, respectively. Highlights: Facile synthesis of CeOx modified NiFe catalysts grown on rGO. The NiFe-CeOx/rGO catalysts exhibit a branched nanodendrit architecture. NiFe-CeOx /rGO exhibits superior catalytic activity dehydrogenation of hydrazine.